2009
DOI: 10.1038/cdd.2009.202
|View full text |Cite
|
Sign up to set email alerts
|

Monoallelic but not biallelic loss of Dicer1 promotes tumorigenesis in vivo

Abstract: Human tumors are characterized by widespread reduction in microRNA (miRNA) expression, although it is unclear how such changes come about and whether they have an etiological role in the disease. Importantly, miRNA knockdown has been shown to enhance the tumorigenic potential of human lung adenocarcinoma cells. A defect in miRNA processing is one possible mechanism for global downregulation. To explore this possibility in more detail in vivo, we have manipulated Dicer1 gene dosage in a mouse model of retinobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
138
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 39 publications
(44 reference statements)
17
138
2
Order By: Relevance
“…Further to this, monoallelic Dicer1 loss exerted an effect, which indicates that Dicer1 is also a haploinsufficient tumor suppressor gene. These findings are consistent with the role of Dicer1 in other tumor types (Arrate et al 2010;Lambertz et al 2010;Nittner et al 2012;Yoshikawa et al 2013;Zhang et al 2014).…”
Section: Dicer1 Positively Corroborates With Sonic Hedgehogpatched Sisupporting
confidence: 81%
“…Further to this, monoallelic Dicer1 loss exerted an effect, which indicates that Dicer1 is also a haploinsufficient tumor suppressor gene. These findings are consistent with the role of Dicer1 in other tumor types (Arrate et al 2010;Lambertz et al 2010;Nittner et al 2012;Yoshikawa et al 2013;Zhang et al 2014).…”
Section: Dicer1 Positively Corroborates With Sonic Hedgehogpatched Sisupporting
confidence: 81%
“…30 Furthermore, hemizygous deletion of DICER1 occurs in 27% of the human cancers, 14 and recent studies have demonstrated that DICER1 is a haploinsufficent tumour suppressor in both lung cancer and retinoblastoma. 13,14 This is supported by a recent report, in which DICER was shown to be specifically targeted by the miR-103/107 family in breast cancer, where overexpression of miR-103/107 members induced epithelial-to-mesenchymal transition via reduced levels of miR-200b. 31 Therefore, direct regulation of DICER1 levels by miR-9 overexpression could contribute to transformation and invasiveness in HL.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, although the function of DICER1 as a key enzyme in miRNA biogenesis is well characterized, recent reports have demonstrated that DICER acts as a haploinsufficent tumour suppressor in lung cancer and retinoblastoma. 13,14 On the other hand, HuR is a well-documented regulator of cytokine expression acting via direct binding to ARE sequence motifs. AREs are short AU-rich sequences in the 3 0 untranslated region (UTR) of several mRNAs, especially cytokines and growth-related genes that affect mRNA stability and translation.…”
Section: Introductionmentioning
confidence: 99%
“…and co-workers discovered that monoallelic loss of Dicer1 had no effect on the normal retinal development of mice, but remarkably accelerated retinoblastoma formation. 29 Frequent hemizygous deletions of DICER1 have been observed in human cancers as well. 29 In addition, Su et al reported that the tumor suppressor p63, a member of the p53 family, binds to the promoter region of the Dicer gene and activates its transcription.…”
Section: -9mentioning
confidence: 99%
“…29 Frequent hemizygous deletions of DICER1 have been observed in human cancers as well. 29 In addition, Su et al reported that the tumor suppressor p63, a member of the p53 family, binds to the promoter region of the Dicer gene and activates its transcription. Knockout of p63 dampens tumor metastasis in mice.…”
Section: -9mentioning
confidence: 99%